2012
DOI: 10.1124/dmd.111.043455
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Expression of Drug-Metabolizing Enzymes by Single-Walled Carbon Nanotubes in Human Respiratory Tract Cells

Abstract: ABSTRACT:Single-walled carbon nanotubes (SWCNTs) have attracted attention for biomedical and biotechnological applications, such as drug delivery. However, there are concerns about the safety of SWCNTs for use in humans. To investigate the potential use of SWCNTs for targeted drug delivery to the lung, we examined their effect on drug-metabolizing enzymes in primary normal human bronchial epithelial (NHBE) cells from two donors and the lung carcinoma A549 cell line. Exposure of NHBE and A549 cells to SWCNTs dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…In particular, genes that are transcriptional targets of Ahr, including CYP1A1, CYP1B1 and ARNT2, were down-regulated by MWCNT and up-regulated by TiO 2 -NB depending on time point and cell type. Both CYP1A1 and CYP1B1 expression and enzymatic activity were previously found to be repressed in human A549, HepG2 or MCF-7 cells after exposure to SWCNT (Hitoshi et al 2012). The authors found that SWCNT inhibited both basal and dioxin-induced P450 levels likely by preventing binding of activated Ahr to enhancer regions for these genes.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, genes that are transcriptional targets of Ahr, including CYP1A1, CYP1B1 and ARNT2, were down-regulated by MWCNT and up-regulated by TiO 2 -NB depending on time point and cell type. Both CYP1A1 and CYP1B1 expression and enzymatic activity were previously found to be repressed in human A549, HepG2 or MCF-7 cells after exposure to SWCNT (Hitoshi et al 2012). The authors found that SWCNT inhibited both basal and dioxin-induced P450 levels likely by preventing binding of activated Ahr to enhancer regions for these genes.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, changes in the expression of drug-metabolizing enzymes, such as CYP1A1, CYP1B1, CYP2S1, and CYP19A1, were observed in human respiratory tract cells (NHBE and A549) after the treatment of SWNTs (100 μg/ mL, 24 h exposure) (Hitoshi et al 2012). Down-regulation of CYP1A1 and CYP1B1 may be, in part, due to the reduced binding of the aryl hydrocarbon receptor (AhR) to the enhancer region of CYP1A1 and CYP1B1 (Hitoshi et al 2012).…”
Section: Pathways Associated With Swnt-induced Toxicitymentioning
confidence: 99%
“…Down-regulation of CYP1A1 and CYP1B1 may be, in part, due to the reduced binding of the aryl hydrocarbon receptor (AhR) to the enhancer region of CYP1A1 and CYP1B1 (Hitoshi et al 2012). The exact mechanism by which SWNTs affect the AhR-CYP axis remains to be further elucidated.…”
Section: Pathways Associated With Swnt-induced Toxicitymentioning
confidence: 99%
“…In fact, several in vitro studies reported the ability of different metal, metal oxide as well as carbon based and polymeric NPs to acutely (after up to 24 h of treatment) or sub-acutely (after up to 48 h of treatment) affect the gene (Alshatwi et al, 2013; Hitoshi et al, 2012; Periasamy et al, 2014) and mRNA expression (Hitoshi et al, 2012; Lammel et al, 2015) as well as the functionality (Christen and Fent, 2012; Fröhlich et al, 2010; Kulthong et al, 2012; Lu et al, 2013; Lamb et al, 2010; Sereemaspun et al, 2008; Warisnoicharoen et al, 2011; Ye et al, 2014) of CYP metabolic enzymes, although with different results maybe in relation to the type and physico-chemical characteristics of the NPs investigated. Moreover, induction or inhibition of CYP450 gene (Balasubramanian et al, 2010; Ji et al, 2009), mRNA (Cui et al, 2010; Sun et al, 2012) and protein expression (Coccini et al, 2013), as well as alterations in its metabolic functionality (Cho et al, 2010; Kulthong et al, 2012) were also reported in in vivo studies under various conditions of exposure involving a series of different NPs (Table 1).…”
Section: Resultsmentioning
confidence: 99%